Особливості урбанізаційного процесу в Україні у ХІХ – на початку ХХ століття (на прикладі м. Слов'янська Харківської губернії) - Закірова, С. (Краєзнавство, 2016)
Розглянуто основні напрямки розвитку Слов'янська у ХІХ – на початку ХХ століття, проаналізовано зміни у чисельності населення, трансформація промислової та соціальної інфраструктури міста. В работе рассмотрены основные направления развития Славянска в ХІХ – начале ХХ веков,
проанализированы изменения численности населения, трансформация промышленной и социальной инфраструктуры города. The article represents the main directions of development of Slavyansk to ХІХ - the beginning of
XX century, іt is analyzed change in population, the transformation of the industrial and social infrastructure
of the city. The article deals with the dynamics of the increase of the city's Slavyansk population,
analyzed the circumstances that contributed to the growth of citizens.
The largest group of industrial enterprises of the city accounted for the plants for mining and processing
mineral resources. A special role in the development of the Slavyansk played mining rock salt.
This sort of production were engaged factories that belong to private entrepreneurs and collective
owners. One of the reasons for the increase of urbanization has been the development of production
of construction materials. In 1913 the city worked in 38 factories of different forms of ownership. The
work of these enterprises demanded increasing the number of workers.
The growing number residents of Slavyansk contributed to a significant change in the social infrastructure
of the city. Positive changes have occurred in the field of education and health care. Rapidly
increasing number of catering establishments, opened apartment houses and hotels. An important indicator
of urbanization was the intensification of transportation in the region, development of road
transport in the city.
The changes affected the life of citizens, the organization of their leisure time. In Slavyansk new
printing plant opened, bookstores, theaters, libraries, cinemas and photo salons.